THE EFFECTIVENESS OF DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL ON NARRATIVE TEXT (ELang | An English Language Education Journal, 2017)
This research paper entitled “The Effectiveness of Dictogloss Technique to Improve Students’ Writing Skill on Narrative Text”. It was intended to fulfill one of the requirements to the English Study Program of FKIP Universitas Bale Bandung for taking find out whether or not Dictogloss technique is effective to improve students’ writing skill on narrative text and to find out the students’ responses toward Dictogloss technique in teaching writing on narrative text. In this research, the writer choosed the second grade of SMP Tunas Baru Ciparay. The number of sample was 30 students for the experimental group and 30 students for the control group. The result of the pre-test showed that the t-test value was 0.472, where t-table at p = 0.05 with Df = N1+N2 – 2= 30 +30 - 2= 58 at the level of significance 0.05 for two tailed, the critical value of t is 2.042. Then, the writer observed that the t observe was lower than t-table (0.372 < 2.042). It means that there was no significant difference between the experimental group and control group before doing the treatment. The result of post-test showed that the t-test value was 2.543, where t-table at p = 0.05 with Df = N1+N2 – 2= 30+30 – 2= 58 at the level of significance for two tailed, the critical value of t is 2.042. as the value of t observe was bigger than that of the t-table (2.534 > 2.042). It means that the Null Hypothesis (Ho) was rejected and the Alternative Hypothesis (Ha) was accepted, stating that there was significant difference in the result between using Dictogloss Technique than the conventional method. The result of Dictogloss technique is effective to the students. The questionnaire was only distributed to the experimental group. It was calculated and converted into percentage to find out the students’ responses toward Dictogloss Technique to complete the data. The result showed that the students have a good response in implementing Dictogloss Technique could help them improve their writing skill on narrative text. It means that almost all of students gave a good result responses towards Dictogloss Technique.Key words: Dictogloss Technique, Narrative Text, Writing Skill